Different strokes for different banks: A heterogeneity analysis of Fed QE on bank lending - Kapoor, Supriya (My University, 2026)
Using detailed data on U.S. bank holding companies and the Federal Reserve’s Quantitative Easing (QE) programmes implemented after the 2007–09 financial crisis, we reveal a more nuanced transmission mechanism than previously documented in the literature. The effect of QE on bank lending varies systematically according to banks’ liquidity and solvency profiles. Specifically, we find that the most vulnerable banks (e.g., those with high asset-risk exposure and low liquidity or low capital positions) tend to increase lending more aggressively than their safer counterparties in response to QE. Moreover, QE appears to increase risk-taking behaviour, especially among weaker banks. These findings highlight the non-linear nature of QE transmission and emphasize the importance of accounting for bank heterogeneity in the assessment of unconventional monetary policy.
PUBLISHED
Keywords: Banking; Finance; Financial economics, Financial and statistical analysis; Macroeconomics, open economy, international; bank lending